Palaeoceanographic and palaeoclimatic changes during the Late Hauterivian-Barremian and their impact on the northern Tethyan margin: a combined sedimentological and geochemical approach - Bodin, Stéphane (My University, 2006)
The goal of this PhD study was to decipher the mechanisms responsible for changes in the carbonate platform factory accompanied by incipient drowning. For this purpose, a peculiar condensed level called the Altmann Member, which recorded the northern Tethyan margin drowning during the latest Hauterivian – Early Barremian, and which is now locked up in the Helvetic realm, was studied. Indeed, this horizon is situated at the verge of a major change in the carbonate platform production mode. On one hand, during the Hauterivian, heterotrophic organisms such as crinoids and bryozoans dominated the northern Tethyan carbonate platforms. On the other hand, phototrophic organisms such as corals, green algae and rudists dominated during the Late Barremian. This important transition and its documentation in the shelf and basinal realms of the Tethys offered the framework of this study. Helvetic realm: A first step was to establish as precisely as possible the time range of the Late Hauterivian – Barremian sediments in the Helvetic realm. Thanks to numerous ammonite findings, it was possible to determine that the Altmann Member spans from the Pseudothurmannia seitzi (latest Hauterivian) to the Coronites darsi (latest Early Barremian) ammonite zones. The onset of the Schrattenkalk Formation is dated by sequence stratigraphy correlation and by ammonite findings in the Chopf Member. This event is dated as belonging to the Gerhardtia sartousiana zone. Sedimentology and sequence stratigraphy studies helped to determine the unfolding of the Altmann Member drowning episode, which has proceeded in two steps. The first one is coeval with the Faraoni event, which was thus far only reported from basinal settings. The second step is coeval with the Barremian second-order sea-level rise occurring at the Early – Late Barremian transition. During the Early Barremian second-order sea-level lowstand, the Helvetic platform was submitted to winnowing currents leading to the formation of phosphatized crusts. Basin sections: In order to understand the link between carbonate platform factory changes and drowning events, geochemical studies were done on bulk-rock and belemnite samples from (hemi-) pelagic sections. These include redox-sensitive trace metals, phosphorus, carbon and oxygen isotopes. Four sections were chosen: the Angles section, SE France, which is the Barremian stratotype section; the Veveyse de Châtel – St. Denis section, Ultrahelvetic realm, Switzerland: the Fiume-Bosso and Gorgo a Cerbara sections, Umbria-Marche basin, Italy. These four sections offer a good coverage of the western Tethys and allow thus to establish general trends in the paleoceanographic conditions of the western Tethys at that time. Enrichments of redox-sensitive trace metals were used to trace oceanic anoxic events during the Late Hauterivian – Early Barremian, because numerous black-shale horizons are recognized in the corresponding rocks. Only one level, corresponding to the Faraoni Level, was identified as the result of an oceanic anoxic event. This result is confirmed by the C/P ratio that shows a positive shift associated to the Faraoni Level. Phosphorus burial rates were used to trace nutrient contents in the ocean during the Late Hauterivian – Barremian. They have resulted in a tripartite division of trophic conditions during the studied time interval. Thus, the middle Late Hauterivian is associated to mesotrophic conditions, the latest Hauterivian – Early Barremian to eutrophic conditions and the Late Barremian to oligotrophic conditions. Bulk rock carbon isotopes were investigated in order to obtain information about the carbon cycle and its link to the carbonate platform. It appears that the bulk-rock carbon isotope signal in basinal sections situated close to the northern Tethyan margin is strongly influenced by carbonate factory changes due to carbonate platform shedding into the basin. During the time of heterozoan-dominated platform growth, the pelagic carbon isotope signal is buffered by the shedding of calcite-dominated fragments and dissolved inorganic carbon. During the time of photozoan-dominated platform growth, the pelagic carbon isotope signal is pushed to heavier values due to the export of aragonite. Finally, in order to better understand the interactions between palaeoenvironmental changes and carbonate platform, an integrated approach, coupling numerous geochemical data as well as clay minerals, sea-level changes and others information, was done. This approach allows to conclude that changes in the northern Tethyan carbonate platform factory were driven by the overall nutrient content in seawater. During times of oligotrophic conditions, photozoan carbonate systems dominated the neritic realm whereas during times of meso-eutrophic conditions, heterozoan carbonate systems developed. Moreover, carbonate platform drowning events were linked to changes in ocean current pattern during time of sea-level highstand, together with high seawater nutrient levels. These changes have favored winnowing of platform-surface sediments and the deposition of phosphate-rich layers, and precluded carbonate platform growth along the northern Tethyan margin.
Thèse de doctorat : Université de Neuchâtel, 2006 ; 1901
Keywords: Hauterivien; Barrémien; marge Nord-Tethysienne; photozoaire; hétérozoaire; ennoiement de plate-forme carbonatée; membre d’Altmann; calcaire Urgonien; biostratigraphie des ammonites; bélemnites; niveau Faraoni; métaux traces sensibles aux conditions redox; taux d’enfouissement du phophore; isotopes du carbone et de l’oxygène; Hauterivian; Barremian; northern Tethyan margin; photozoan; heterozoan; carbonate platform drowning; Altmann Member; Urgonian limestone; ammonite biostratigraphy; belemnites; Faraoni Level; redox-sensitive trace metals; phosphorus burial rates; carbon and oxygen isotopes